Menjembatani Kompetensi Digital dan Kinerja Tendik Gen Z di UnmuhJember melalui Etika Kerja - Septy Holisa Umamy; Januariya Laili; Saibah Saibah (LPPM Universitas Bina Sarana Informatika, 2025)
This research aims to examine the impact of digital competence on the performance of Generation Z educational staff at Unmuh Jember, with work ethics serving as an intervening variable. This issue is crucial because Generation Z, often referred to as digital natives, possesses strong technological skills. However, these competencies do not always directly enhance performance without being accompanied by solid work ethics. A quantitative research approach was applied using a survey method, involving Generation Z educational staff at Unmuh Jember as participants. The study's population and sample comprised 52 respondents, all categorized as Generation Z educational staff. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique to assess the relationships between variables the findings indicate that, first, digital competence does not have a direct impact on educational staff performance. Second, digital competence positively influences work ethics. Third, work ethics significantly affect the performance of educational staff. Fourth, work ethics act as a mediating factor, facilitating the influence of digital competence on performance. This suggests that digital competence can enhance performance only when work ethics are present as an intermediary. This study offers both theoretical and practical insights by highlighting the crucial role of work ethics in optimizing the effect of digital competence on performance. Based on these findings, it is recommended to reinforce an ethical work culture and design training programs that integrate digital skills with ethical values. Future research could expand variable coverage, employ longitudinal methods, or conduct comparative studies across different generational cohorts to gain deeper insights.